Silviculture from the ecological-conservational point of view - Donoso Zegers, Claudio (Bosque (Valdivia), 1989)
The concept of silviculture is analized stressing its scientific basis as basic silviculture or forest ecology. The fact that the concept of conservation, implicit in the definition of silviculture, refers to obtaining a continuous production is stressed. How the scientific ecological basis impinges on silviculture, which are the objectives of conservation and how they should be accomplished in order to practice silviculture are discussed.